Systematic Evaluation of Antimicrobial Efficacy in Phytochemical Extracts - Yadav, Amit Kumar (Journal of Research in Science and Engineering, 2025)
This research paper aims to test the antibiotic properties of natural substances to see if they can be viable replacements for antibiotic skin medications. The aim was to determine if these commonly used natural remedies could effectively inhibit bacterial growth on the skin, simulating a bacterial infection in a controlled lab setting using agar plates. It therefore offers alternatives to people who may not have access to antibacterial medications and to avoid the overuse of medications. Through incubation of E.coli bacteria, it found that hand sanitiser and garlic both had antibacterial properties and inhibited the growth of the bacteria. It also found that Triben, an antifungal medication can not be used to replace antibacterial medications. Further experimentation is recommended to test the antibiotic properties of garlic and apple cider vinegar as no concrete conclusions were drawn for these substances. The findings highlight that while certain home remedies might have potential antibacterial properties, their effectiveness is not universally reliable, and further research is needed to explore their use against various bacterial infections.